Good government and sustainable anti-corruption strategies a role for independent anti-corruption agencies? - Doig, Alan (1995)
"Aid donors are increasingly seeking to link assistance to sustainable reform, including the provision of a responsible and responsive political and legal framework, the improvement of recipient countries' social, health and educational prospects, and the promotion of economic development and liberalization. Much attention is given to the first of these because of the size and cost to the state and the perceived constraints it exercises on the longer-term changes to the economy and society; in general terms, good government is an essential precondition for good governance and economic development. Increasingly donors have focused on corruption, both as a core obstacle to the encouragement of good government, and on the steps taken to dealing with it as evidence of commitment and the will of recipient countries to their introduction. While the types of activity associated with corruption are readily identifiable, as are the means to attempt to deal with it, it is usually much more difficult to determine effective implementation, particularly with limited resources at a time when longer-term political and economic reforms are also being promoted. It is therefore especially important that, in relation to corruption and good government, a practicable, effective and sustainable means is available to deal with corruption from preventative, investigative and reform perspectives"
Keywords: Sustainable development; Economic development; Political corruption; Corruption